2013
DOI: 10.1080/10937404.2013.769418
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation And Risk Assessment Ofd-Limonene

Abstract: d-Limonene, a major constituent of citrus oils, is a monoterpene widely used as a flavor/fragrance additive in cosmetics, foods, and industrial solvents as it possesses a pleasant lemon-like odor. d-Limonene has been designated as a chemical with low toxicity based upon lethal dose (LD50) and repeated-dose toxicity studies when administered orally to animals. However, skin irritation or sensitizing potential was reported following widespread use of this agent in various consumer products. In experimental anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 72 publications
2
88
0
1
Order By: Relevance
“…(+)-Limonene, the enantiomer of orange and lemon peels, has a lemon-like odor making it attractive as an additive in cosmetics and foods (Kim et al 2013). This enantiomer is the most abundant in plants.…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…(+)-Limonene, the enantiomer of orange and lemon peels, has a lemon-like odor making it attractive as an additive in cosmetics and foods (Kim et al 2013). This enantiomer is the most abundant in plants.…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…Although, d-Limonene has been designated as a chemical with low toxicity based upon lethal dose (LD 50 ) and repeated-dose toxicity studies when administered orally to animals, skin irritation or sensitizing potential was reported following widespread use of this agent in various consumer products [37]. Vapor pressure for 2-tridecanone and d-limonene is 0.0164 and 1.96 mmHg at 25˚C respectively, indicating that 2-tridecanone is much less volatile than d-limonene, indicating that 2-tridecanone will cause less potential vapor hazard in work places.…”
Section: Discussionmentioning
confidence: 99%
“…This compound has a low toxicity profile and has been shown to be safe when used in humans. Adverse effects reported include skin irritation when D-limonene was used in cosmetic products (Kim et al, 2013). As a systemic therapy, this compound has been used in humans in clinical trials at up to 15 gm/day without major toxicities being observed.…”
Section: Discussionmentioning
confidence: 99%